2022
DOI: 10.1088/2053-1591/ac4f88
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the tensile and modal properties of epoxy based symmetric interlayer glass/carbon hybrid composites

Abstract: Interlayer hybrid composites can be tailored for enhanced strength and stiffness. Research on enhancing the mechanical properties of Interlayer hybrid composites is being explored by varying fiber orientations, layup sequence, different type of fiber materials. The objective of this work is to investigate the effect of stacking sequence of the high modulus carbon fibers on the tensile and modal properties of symmetric glass/carbon fiber interlayer composite. The interlayer hybrid composites were fabricated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, the maximum one in the quasi group is for the laminate Q2 and equal to 20.25 Hz as shown in Fig. 5 because the flexural modulus of the arrangement of GGCCCCGG organized by two glass plies at the outer surface is higher than that of the arrangement GCCGGCCG as shown in Table 5 which is different from the results of studies [6] and [17]. The element Q11, Q12, and Q66 of [Q ij ] matrix for 90º glass fibre is higher than that for 90 o carbon.…”
Section: Laminates Manufacturingcontrasting
confidence: 57%
See 1 more Smart Citation
“…On the other hand, the maximum one in the quasi group is for the laminate Q2 and equal to 20.25 Hz as shown in Fig. 5 because the flexural modulus of the arrangement of GGCCCCGG organized by two glass plies at the outer surface is higher than that of the arrangement GCCGGCCG as shown in Table 5 which is different from the results of studies [6] and [17]. The element Q11, Q12, and Q66 of [Q ij ] matrix for 90º glass fibre is higher than that for 90 o carbon.…”
Section: Laminates Manufacturingcontrasting
confidence: 57%
“…In contrast, altering the arrangement by putting the carbon fibre on the external surface for the arrangement CC1[C/G/C/G/C/ G/C/G] s will slightly reduce both the natural frequency and damping ratio to 45 Hz and 0.088, respectively. Pujar et al [6] investigated the tensile and dynamic properties for laminated composite that is fabricated from 80 % glass and 20 % carbon. They found that H3[G/G/G/G/C] s has maximum tensile strength and modulus because of the presence of one carbon ply in the middle of the laminate.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the water absorption depend on the water absorption behavior of different fibers and also mainly attribute the consolidative effects of micropores, matrix / fiber interface adhesion, micropores, and presence of voids in the composites. [ 54,55 ]…”
Section: Results and Discussion (Try To Cite More Literature In Suppo...mentioning
confidence: 99%
“…When interlayer type hybridization is used, its effectiveness is determined by the type of appropriate selection of fibrous materials and their arrangement order. Pujar et al [38] conducted a study on improving the tensile strength of epoxy-glass composites by introducing carbon fabric. For this purpose, they made four 10-layer composites using the vacuum bag method.…”
Section: Hybrydowe Kompozyty Polimerowe O Zwiększonej Absorpcji Energiimentioning
confidence: 99%